The study of photosynthesis pigments of night-scented stock (Matthiola bicornis (Sibth. & Sm.) DC.) raw materials and antimicrobial activity of extracts based on it - Pinkevich, Viktoria; Zhuravel, Irina; Osolodchenko, Tetyana (Annals of Mechnikov’s Institute, 2021)
It is known from the literature that pigments exhibit a variety of pharmacological activity. For example, chlorophyll has antimicrobial, anti-inflammatory and antioxidant properties, regulates the work of heart, neuromuscular system, and has a tonic effect on the body. Carotenoids contribute to the normalization of metabolism, have provitamin, antioxidant, radioprotective and anticancer activities, which together have a positive effect on immunity. They also participate in redox reactions, maintain a normal level of oxygen consumption by body tissues. Against this background, the study of this class of biologically active substances is important. The aim of the study was to determine the quantitative content of chlorophyll a, b and carotenoids in threshed grass and stalks of Matthiola bicornis (Sibth. & Sm.) DC. Tsarytsia Nochi (Queen of Night) and Vechirnii Aromat (Evening Scent) cultivars, and screening of antimicrobial activity of extracts based on its raw materials. Determination of the content of chlorophylls and carotenoids in the studied types of raw materials was carried out by spectrophotometric method without their prior separation. Ethanol (96%) was used to isolate the pigments. The extraction was performed with pre-cooled solvent in a dark place according to the method specified in the scientific works of domestic scientists. To calculate the concentrations of chlorophyll a, b and carotenoids in each of the samples determined their optical density spectrophotometrically at wavelengths corresponding to the maxima of the absorption spectrum of the studied pigments in this solvent. The content of each of the plant pigments was calculated according to known formulas given in the literature. To determine the antimicrobial activity, ethanolic extracts of Matthiola bicornis (Sibth. & Sm.) DC grass were obtained by exhaustive extraction under heating in a ratio of raw material-extractant of 1:50. Ethanol (70% and 96%) were used as extractants. After extraction, the extracts were evaporated in vacuum to completely remove the solvent. The study of antimicrobial activity was performed by the method of diffusion into agar with the definition of zones of growth retardation of microorganisms in the State Institution «Institute of Microbiology and Immunology I. I. Mechnikov National Academy of Medical Sciences of Ukraine», Kharkiv under the leadership of the head of laboratory «Biochemistry of microorganisms and nutrient media», Candidate of Biological Sciences Osolodchenko T. P. In accordance with WHO recommendations to assess the antibacterial activity used the following museum test strains of microorganisms: Staphylococcus aureus АТСС 25923, Escherichia coli АТСС 25922, Pseudomonas aeruginosa АТСС 27853, Bacillus subtilis АТСС 6633 and Proteus vulgaris ATCC 4636. Antimycotic activity was investigated on the test strain Candida albicans АТСС 885/653. To interpret the results, we used the criteria used in the evaluation of new antibacterial substances and the study of antibiotic-resistant strains. The content of chlorophyll a was 1,17±0,06 mg/g, 1,30±0,06 mg/g, 0,31±0,02 mg/g and 0,39±0,02 mg/g, chlorophyll b − 0,64±0,03 mg/g, 00,65±0,06 mg/g, 0,24±0,02 mg/g та 0,31±0,02 mg/g and carotenoids − 0,14±0,02 mg/g, 0,12±0,01 mg/g, 0,03±0,01 mg/g та 0,03±0,01 mg/g in threshed grass and stalks of Night-scented stock, cultivars Queen of Night and Evening Scent respectively. The study of antimicrobial activity of ethanolic extracts of Matthiola bicornis (Sibth. & Sm.) DC grass showed that the diameters of the zones of growth retardation of microorganisms were from 15±0,69 to 23±1,02 millimeters. According to the criteria used in the evaluation of new antibacterial substances and the study of antibiotic-resistant strains, growth retardation zones with a diameter of 15-25 millimeters are regarded as an indicator of sensitivity of the microorganism to the test drug and demonstrate its moderate antimicrobial activity. The obtained results can be further used in the development of quality control methods for the studied raw materials and indicate that Matthiola bicornis (Sibth. & Sm.) DC is a promising raw material for further in-depth pharmacognostic study and development of new drugs based on it. DOI: 10.5281/zenodo.5499638